Optimization of base crystals for silicon solar cells of various destinations - Kirichenko, M.V.; Tymchuk, I.T.; Antova, V.A.; Klochko, N.P.; Kopach, V.R.; Listratenko, A.M. (Functional Materials, 2007)
The spectral dependences of reflection coefficient R(λ) for various light-receiving surface texture types ("inverted pyramids" and "V-grooves") of single crystal silicon wafers are presented as well as output and diode parameters of solar cells (SC) with p- and n-type silicon base crystals (Si-BC). Basing on comparative analysis of R(λ) dependences, the selection of an optimum type of Si-BC light-receiving surface texture is substantiated. Comparing the output and diode parameters of SC with Si-BC of p- and n-type conductivity, the development expediency of high-efficiency Si-SC with the n-type conductivity single crystals is substantiated.